Produksi Bersih Pengolahan Limbah Cair Menggunakan Decanter pada PT Aetra Air Jakarta - Sukwika, Tatan; Muhammad, Said Azmi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2021)
ABSTRACT Clean water process production by PT Aetra Air Jakarta (AAJ) emits a lot of wastewater. All this time, a sludge drying bed is used for its production activities, where the sludge produced is not proportional to the area and length of drying time, so the unsatisfied sludge is eventually dumped into the water body. In line with the need to improve the quality of operational activities, clean water service providers are trying to create zero waste. They are environmentally friendly through the use of a decanter. The research objective was to determine the amount of sludge treated in the wastewater treatment process and measure water removal efficiency in sludge using a decanter. Methods of data collection through observation and testing of wastewater treatment using a decanter. The decanter treatment process starts from taking the sludge sample before it is processed; the sludge treatment process begins entering the decanter until the sludge is finished processing. The results showed that the average volume of sludge was 24.84 m3, and the water removal efficiency was between 89â€“91%. The conclusion is that the set inflow rate is directly proportional to TSS while the efficiency of TSS water removal in the sludge is smaller so that the use of a decanter is greater. It recommended that the residual processing sludge be used as raw material for fertilizer production. The Pb and Zn content in the sludge does not exceed the quality standard. Keywords: decanter, clean production, TSS, sludge volume Â ABSTRAK Air bersih yang diproduksi oleh PT Aetra Air Jakarta (AAJ) mengeluarkan banyak limbah cair. Selama ini, kegiatan produksinya digunakan sludge drying bed, dimana lumpur yang dihasilkan tidak sebanding dengan luas dan lamanya waktu pengeringan, sehingga lumpur yang tidak tertampung akhirnya terbuang ke badan air. Seiring kebutuhan perbaikan kualitas kegiatan operasional, penyedia layanan air bersih berupaya menciptakan zero waste dan ramah lingkungan melalui penggunaan decanter. Tujuan penelitian menentukan jumlah lumpur yang diolah pada proses pengolahan limbah cair dan mengukur efisiensi penyisihan air pada limbah lumpur menggunakan alat decanter. Metode pengumpulan data melalui pengamatan dan pengujian pengolahan limbah cair menggunakan decanter. Proses pengolahan decanter dimulai dari pengambilan sampel lumpur sebelum diolah, proses pengolahan lumpur dari awal masuk ke decanter sampai lumpur selesai diolah. Hasil penelitian menunjukkan rata-rata volume lumpur sebesar 24,84 m3, dan efisiensi penyisihan air antara 89â€“91%. Kesimpulannya adalah set inflow rate berbanding lurus dengan TSS sedangkan efisiensi penyisihan air TSS pada limbah lumpur semakin kecil sehingga penggunaan decanter menjadi lebih besar. Direkomendasikan agar lumpur sisa pengolahan dimanfaatkan sebagai bahan baku untuk pembuatan pupuk dengan syarat kandungan Pb dan Zn dalam lumpur tidak melebihi baku mutu. Kata kunci: decanter, produksi bersih, TSS, volume lumpur